Leadership of the Chairperson of the Foundation at the Kahirurrosyidin Foundation, East Lombok - Baiq Widayung; Asrin Asrin; Muntari Muntari (MANAZHIM, 2023)
This study aims to describe the leadership model and communication patterns of the chairman of the foundation in developing the performance of school principals and teachers. This research uses a qualitative approach with a case study method. Data collection techniques were carried out through interviews, observation, and documentation studies. The informants in this study were foundation heads, school principals, teachers, education staff, and the development team. Data analysis techniques by means of coding. The results of the study found that: (1) The efforts of the chairman of the foundation in improving the performance of school principals and teachers at the East Lombok Khairurrosyidin Foundation are by applying a transformational leadership model and planning all school programs in a participatory and coordinative manner, solving problems and making decisions together, leading and mobilizing subordinates objectively, using formal and informal power, disposing tasks proportionally, building solidarity, setting an example, building transparency, encouraging continuation of studies, conducting comparative studies, education and training, assisting problem solving, and providing rewards. (2) The pattern of communication used by the chairman of the foundation in improving the performance of school principals and teachers at the East Lombok Khairurrosyidin Foundation is direct or face-to-face communication using oral methods accompanied by writing and supported by persuasive communication so that there is harmony between formal and informal communication.